2019
DOI: 10.22146/jik.52433
|View full text |Cite
|
Sign up to set email alerts
|

Dinamika Suksesi Vegetasi pada Areal Pasca Perladangan Berpindah di Kalimantan Tengah

Abstract: Indonesia's forests is the third largest tropical forest after Brazil and Africa. However, the high rate of forest degradation in Indonesia led this country become one of the most largest contributor of greenhouse gas emissions in the world. One of the causes of the degradation of tropical forest in Indonesia is the shifting cultivation practice. The succession of vegetation after shifting cultivation practice can provide ecological services such as increasing vegetation cover and improving soil properties but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 5 publications
1
5
0
5
Order By: Relevance
“…In balukar anum and jurungan, the vegetation was mostly dominated by several types of pioneer species such as sungkai (P. canescens), lua (Ficus variegata), and several species of Artocarpus such as tarap (Artocarpus elasticus) and tiwadak (A. champeden). This finding is in accordance with the research by Maulana (2019) which found that young fallow lands with an age of 9 years old are dominated by pioneer plants such as Ficus spp. and Artocarpus spp.…”
Section: Discussionsupporting
confidence: 93%
“…In balukar anum and jurungan, the vegetation was mostly dominated by several types of pioneer species such as sungkai (P. canescens), lua (Ficus variegata), and several species of Artocarpus such as tarap (Artocarpus elasticus) and tiwadak (A. champeden). This finding is in accordance with the research by Maulana (2019) which found that young fallow lands with an age of 9 years old are dominated by pioneer plants such as Ficus spp. and Artocarpus spp.…”
Section: Discussionsupporting
confidence: 93%
“…Several analyses on biodiversity indicators were conducted including Margalef species richness index (Magurran 1988;Odum 1996;Maulana et al 2019), Sorensen similarity index based on Sorenson formula (1948) as in Odum (1996), Shannon-Wiener diversity index (H') (Krebs 1994;Pamoengkas et al 2018;Maulana et al 2019), and Pielou evenness index (Odum 1996;Maulana et al 2019). Analysis on interspecies relationship between merbau and other species was determined using contingency tables (Greig-Smith 1983;Maulana et al 2019) with Chi-square formula at confident interval of 5 % (Ludwig and Reynolds 1988;Sirami et al 2019). Soil analysis was conducted at the Agricultural Technology Assessment Center (BPTP) Yogyakarta to analyze soil chemistry (pH (H2O), C-organic and CEC), essential macronutrients (P and K available, Ca and Mg,) and essential micronutrients (Fe, Mn, and Zn) with total 45 samples.…”
Section: Discussionmentioning
confidence: 99%
“…The evenness index on the three sites ranged from 0.86-0.94 for seedling stage, 0.91-0.96 for sapling stage, 0.87-0.93 for pole stage, and 0.89-0.93 for trees. This indicates that the vegetation diversity in all three locations was evenly distributed since the E value > 0.6 (Maggurran 1988;Brower et al 1998;Maulana et al 2019;Fitri et al 2020).…”
Section: Biodiversity Indicators Of Vegetation Community In Merbau Habitatmentioning
confidence: 94%
“…Sumber daya hutan di Indonesia merupakan salah satu yang terkaya di dunia. Keragaman hayati yang sangat tinggi berupa fauna dan flora merupakan uraian kebermanfaatan atas konsekuensi Indonesia sebagai negara dengan hutan tropis terbesar ketiga setelah Brazil dan Zaire (Maulana et al, 2019). Peranan sumber daya hutan ini dapat termanifestasikan dari produk yang dihasilkan.…”
Section: Latar Belakangunclassified